Emergency preparedness in industrial plants: an industry 4.0 driven training solution - Padovano, Antonio; Furgiuele, Franco; Longo, Francesco (My University, 2019)
Major accident hazards industrial sites or high-risk industries lack of a dedicated training methodology and environment to enhance significantly the personnel rate of retention as well as emergency preparedness and response skills (both technical and non-technical, e.g. leadership, decision-making, team-working, stress management). The need for effective industrial emergency preparedness and response training systems is widely acknowledged also from academic communities that have invested a great deal of time and effort to detect methodologies to enhance emergency response staff performance (emergency manager and emergency team members). This study takes a step forward in current practice proposing a multiplayer industrial emergency preparedness and response training system, which leverages on Industry 4.0 enabling technologies – namely Simulation, Virtual Reality & Serious Games – and on a cooperative, experiential and differentiated training strategy. It also pushes for an increased attention on human factors in the Occupational Health and Safety 4.0 and proposes an approach to analyze the effects of human factors with the ultimate aim to include them in the design of industrial safety protocols and regulations and in the assessment of hazards. This way, after an experimental campaign and statistical analysis of the results, the proposed training system has been critically investigated to ascertain: § how the emergency response staff performance evolves along repeated training sessions; § to which extent the proposed solution is effective in delivering procedural knowledge to the emergency response staff; § whether it is realistic enough to think that the training experience produces psychological stress in those people that are trained with it and how they cope with stress over the repeated replications § whether and to which extent human factors, such as stress and perceived workload, are correlated to the capability of the emergency manager to coordinate and monitor the execution of all the measures and actions intended to deal with an industrial accident and its effects.
Dottorato di Ricerca in Ingegneria Civile ed Industriale, Ciclo XXXI
Keywords: Emergency management; Innovative technology